2022
DOI: 10.1002/adma.202109354
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Chiral Nanoparticles to Target NK Cells and CD8+ T Cells for Cancer Immunotherapy

Abstract: The chirality of nanomaterials (nanoparticles, NPs) can influence their interaction with cells and biological systems. However, how chirality can exert impact on the immune response has yet to be investigated. Here, the immunological effect of chiral nanomaterials is investigated as a therapeutic and preventive option against tumors. Compared with achiral nanoparticles, chiral NPs with a g‐factor of 0.44 are shown to enhance both innate and acquired immunity against tumor growth. It is also found that chiral N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 60 publications
(79 reference statements)
0
66
0
Order By: Relevance
“…[26][27][28] The different interactions of chiral nanoparticles (NPs) with bio-interfaces can induce a range of biological reactions. 27,29,30 Our group has made several key breakthroughs in this eld. For example, we found that the maturation of immune cells can be regulated by nanoscale chirality via differential affinities for biological receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The different interactions of chiral nanoparticles (NPs) with bio-interfaces can induce a range of biological reactions. 27,29,30 Our group has made several key breakthroughs in this eld. For example, we found that the maturation of immune cells can be regulated by nanoscale chirality via differential affinities for biological receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunotherapy, which aims to eliminate cancer cells by the host immune system, has attracted significant attention during the past decade ( Wang W. et al, 2022b ; Peng et al, 2022 ). Among different cancer immunotherapy strategies, immune checkpoint blockade has shown significant clinical effects in many tumors ( Sharpe and Pauken, 2018 ).…”
Section: Exosome-mimicsmentioning
confidence: 99%
“…In addition to inducing autophagy and the apoptosis of tumor cells via the photothermal effect as part of tumor therapies, there exist some anti-tumor effects of chiral self-assembled structures that focus on immune-induced responses. For example, Wang et al obtained prismatic cube-shaped chiral nanoparticles by adding chiral molecules to gold nanoparticles and found that L-NPs could significantly inhibit tumor growth in C57BL6 mice and improve their survival rate [ 111 ]. The study also found that the mechanism underlying this phenomenon was that the L-NPs stimulated innate immunity by activating natural killer (NK) and CD8 + T cells and enhanced acquired immunity.…”
Section: Medical Applications Of Biomimetic Chiral Self-assembled Par...mentioning
confidence: 99%